(untitled) (Research, Society and Development, 2025)
This study aimed to synthesize the most recent evidence on the relationship between nutrition and osteoporosis in postmenopause, highlighting the effectiveness of nutritional interventions and supplementation. It seeks to provide a comprehensive view, identify knowledge gaps, and guide future research and clinical practices. A narrative review of the recent scientific literature on the effect of calcium and vitamin D supplementation on bone mineral density in postmenopausal women was conducted, also considering the combination of these interventions with physical activities. The results indicated that calcium and vitamin D supplementation presented significant benefits, not only in maintaining bone mineral density but also in reducing the risk of fractures, especially when combined with physical exercises focused on improving muscle strength and balance. Practices such as yoga and functional training proved effective in reducing the risk of falls. It is concluded that calcium and vitamin D supplementation, combined with physical exercise programs, represents an effective approach in preventing fractures and strengthening bones in postmenopausal women. However, it is essential to personalize treatment, and continued research on the impact of nutrition in this population is crucial to optimize bone health care.